THE INFLUENCE OF THE INTENSITY OF INTERNET MEDIA USAGE AND LEARNING MOTIVATION ON INCREASING LEARNING OUTCOMES OF BOGA DASAR SUBJECTS FOR GRADE X STUDENTS AT SMK NEGERI 57 JAKARTA - Evy Fardia; Mahdiyah -; Ridawati - (International Journal of Education, Information Technology, and Others, 2019)
Purpose of this study is to examine the intensity of internet media usage and learning motivation towards improving student learning outcomes and strengthen theories related to learning motivation, intensity of internet media usage to improve student learning outcomes. This study was conducted at SMK 57 Jakarta using a quantitative approach with survey method. The target population is students of 57 Jakarta Vocational School majoring in Catering, while the affordable population is students of class X (ten) SMK Negeri 57 Jakarta 2017-2018 academic year totaling 139 people and 103 students as research samples using Slovin formula. Data analysis techniques used in this research is with descriptive and inferential statistics which are Regression Linearity Tests. Based on the results of the analysis above it can be concluded that there is no significant influence between the intensity of Internet Media Usage on Basic Food Subject Learning Outcomes. Based on the results of the above analysis it can be concluded that there is no significant effect between Student learning Motivation on Basic Food Subject Learning Outcomes. Based on the results of the analysis above it can be concluded that there is no significant effect between the intensity of Internet Media Usage and Learning Motivation simultaneously on Basic Food Subject Learning Outcomes.